Finite-time parameters estimation of the Chua system - Chiaravalloti,F; D'Alfonso,L; D'Aquila,G; Fedele,G; Parisini,T; Pin,G (American Institute of Physics Publising LLC, 2016)
In this work, the unknown set of parameters of the Chua system is recovered under the hypothesys that the voltages of the capacitors are available. To this end, focusing on the differential equations, the Volterra kernel-based approach is used to perform an estimation without the uncertainty of the unmeasurable derivatives and the unknown initial conditions.